Care to patients with oral problems during COVID-19: a challenge to the professionals of the health sector - Liuba González Espangler; Franklin Lafargue Gainza; Melba Alina Borges Toirac; Lázaro Ibrahim Romero García (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: Care to patients with problems of oral health in times of the COVID-19 has its particularities due to the associated risks.  Objective: To characterize patients with problems of oral health and the professionals team involved in their care during this epidemic period and to describe the biosafety measures assumed.  Methods:   An observational, descriptive and cross-sectional study was carried out in Mártires del Moncada  Stomatology Clinic  in Santiago de Cuba, during April, 2020, for which two random samples were analyzed (patients and professionals). The selected variables were: age, sex, type of emergency, problem of oral health, treatment and professional category.  Results: There was a prevalence of females (61.8 %) and the 19-35 age group (41.6 %) and 64.8 % of them corresponded to the basic services.  Conclusions: The problems of oral health during this period were characteristic of the basic services, with an increment of the orthodontic and prosthetics services.